Wide frequency band assessment of 28 nm FDSOI technology platform for analogue and RF applications. (June 2015) - Makovejev, S.; Kazemi Esfeh, B.; Barral, V.; Planes, N.; Haond, M.; Flandre, D.; Raskin, J.-P.; Kilchytska, V.
Abstract: This work presents an in-depth wide-frequency band assessment of 28 nm FDSOI MOSFETs for analogue and RF applications. The focus is mainly on such figures of merit (FoM) as the transconductance gm, the output conductance gd, the intrinsic gain Av and the cut-off frequencies fT and f max . Firstly, 28 nm FDSOI MOSFETs are compared with other advanced devices and are shown to outperform them. Secondly, gm – Av analogue metric is demonstrated to be affected by operation frequency. Small-signal parameters variation is limited and dominated by self-heating effect. This is in contrast to the first generation of ultra-thin body and BOX devices without a ground plane where coupling through the substrate has a considerable effect. Thirdly, the self-heating effect is analysed and shown to be smaller than previously predicted by simulations for such devices. Fourthly, it is shown that fT of ∼280 GHz and f max of ∼250 GHz are reachable in the shortest devices. These values are compared to those of the first generation of UTBB devices through the effect of parasitic elements.